Sinergi Pengelolaan Wakaf Tanah Dan Wakaf Uang Untuk Pembangunan Rumah Sakit Dihubungkan Dengan Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf - Pieri Ananda Hiswi; Helza Nova Lita; Hazar Kusmayanti (Asosiasi Pengajar dan Peneliti Hukum Ekonomi Islam Indonesia (APPHEISI), 2020)
Waqf in Indonesian positive law accommodates the development of waqf objects and their designations. Waqf for hospital development is a form of development of the allocation of productive waqf assets with a model of empowering waqf land for the establishment of hospitals and cash waqf for funding its establishment. This article examines both the integration of land and cash waqf models for the establishment of hospitals with normative juridical research methods with analytical descriptive specifications. The position of the hospital resulting from the synergy of land waqf and cash waqf is in line with the objectives mandated in Article 22 of the Waqf Law. The implementation of Hospital Development through the synergy of waqf has the concept of a two-Nazhir partnership as regulated in Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006, which provides benefits for patient financing for the poor. Keywords: Hospital, Productive Waqf, Synergy. Abstrak Wakaf dalam Hukum positif Indonesia mengakomodir perkembangan objek wakaf serta peruntukannya. Wakaf pembangunan Rumah Sakit merupakan bentuk perkembangan peruntukan harta Wakaf produktif dengan model pemberdayaannya tanah wakaf untuk pendirian rumah sakit dan wakaf uang untuk pendanaan pendiriannya. Artikel ini menelaah kedua integrasi model wakaf tanah dan uang untuk pendirian rumah sakit dengan Metode penelitian yuridis normatif dengan Spesifikasi deskriptif analitis. Kedudukan Rumah Sakit hasil sinergi wakaf tanah dan wakaf uang selaras dengan tujuan yang diamanatkan dalam Pasal 22 UU Wakaf. Pelaksanaan Pembangunan Rumah Sakit melalui sinergi wakaf tersebut berkonsep kemitraan dua nazhir yang diatur dalam Undang Undang Nomor 41 tahun 2004 tentang Wakaf dan Peraturan Pemerintah Nomor 42 Tahun 2006, yang peruntukannya memberikan manfaat pembiayaan pasien bagi kaum dhuafa. Kata kunci: Rumah Sakit, Sinergi, Wakaf Produktif.